The power of media and its impact on the child between the educational and entertai (مجلة إحالات, 2026)
Children’s literature is an educational medium that provides children with theopportunity to achieve self-confidence, freedom from the usual methods of thinking fordiscovery, and the interaction with modern digital media. As we are witnessing the challengesof globalization, e-culture has left a clear mark on the stage of life and penetrated sectors ofsociety. It has also created a massive coup in which individual relations with the world havebeen touched by the concepts of the universe and the traditional frameworks of time. Thewhole world has become a complex network of interactions that transcend borders throughrapid communication that acquires the child emotionally and mentally. so we tried tohighlight the causes and manifestations of the fluctuation of the personality of the Arab's childin the light of the current -culture progression. Also, it aimsatsuggesting solutions that helprebuilding a balanced personality and seek to promote children’s literature in both form andcontent.